Assessment of sports nutrition knowledge and dietary habits among collegiate athletes - Balderama, Romeo Miguel A. 1999-
The lack of nutrition knowledge and poor dietary habit effects have been associated with a low or excessive dietary intake that affects sports performance and recovery of collegiate athletes. This study assessed nutrition knowledge and dietary habits using the Filipino Dietary Habits and Nutrition Knowledge Questionnaire and identified collegiate athletes' sources of nutrition information. There were 30 athlete-respondents (15 male and 15 female) in the Swimming and Track and Field teams from a State University. Independent T-test compared the differences between gender and Pearson Product Moment Correlation determined the relationship between dietary habits and nutrition knowledge. All statistical analyses were performed using IBM Statistical Package for Social Sciences (SPSS) Software Version 29. The results have shown that male athletes achieved 71.85% and female athletes 69.44% in nutrition knowledge. While in dietary habits, male athletes got 74.36%, and female athletes got 77.24%. Both genders achieved a good percentage score, and no significant difference was found. Furthermore, there was no significant relationship between dietary habits and nutrition knowledge, the value of the correlation coefficient (r- -0.190) and the p-value (p=0.315) was greater than the significance level of 0.05. Most often sources of nutrition information for the athletes were courses in school, strength and conditioning coaches, social media, and parents. As a result, this research recommends that registered dietitians should be provided for nutrition consultations to further improve athletes’ nutritional intake for better performance and enhance recovery